Adoption as a means of child protection: the law and practice in Malaysia - Mohd, Azizah (Taylor & Francis Group, 2012)
Adoption in Malaysia is of two kinds; firstly, taking the child of another as a person’s own child, where as a result, the adopted child will stand in equal footing with the natural children of the adoptive parents; and secondly, taking a child of another into a person’s custody without affecting the biological status of the adopted child. This article wishes to discuss the law and practice of adoption in Malaysia as one of the means of child protection. The article will also examine as to whether the law is adequate to protect children who are the subjects of adoption.